1983
DOI: 10.1139/y83-034
|View full text |Cite
|
Sign up to set email alerts
|

Glucose homeostasis during the early stages of liver regeneration in fasted rats

Abstract: Kinetic studies with [2-3H]glucose in vivo and gluconeogenic activity measurements in vivo and in vitro were performed in 70% hepatectomized rats submitted to fasting, which represents an extra burden for glucose synthesis but does not impair liver regeneration. Rates of glucose replacement, under steady-state conditions, 14 and 24 h postoperatively, did not differ in partially hepatectomized fasted rats and sham-operated controls. Phosphoenolpyruvate carboxykinase activities increased more rapidly during fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…No change in lactate metabolism has been demonstrated following recovery from partial hepatectomy in either rats [49] or humans [25], implying that the liver has a large functional reserve under physiological conditions of lactate production. However, the effects of intra-operative stress on hepatic glucose homeostasis have not been assessed, particularly when in combination with an extended hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…No change in lactate metabolism has been demonstrated following recovery from partial hepatectomy in either rats [49] or humans [25], implying that the liver has a large functional reserve under physiological conditions of lactate production. However, the effects of intra-operative stress on hepatic glucose homeostasis have not been assessed, particularly when in combination with an extended hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that after partial hepatectomy the decrease in liver tissue is accompanied by complex hormonal changes which produce an increase in glycogenolysis and gluconeogenesis in the liver remnant, together with a decrease in glycolysis, in order to maintain the blood glucose concentration [3][4][5]. During this process, the gene expression of glycolytic/gluconeogenic enzymes would also be modified.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important functions of the liver is the maintenance of glucose homoeostasis. This mechanism operates in different physiological conditions [1,2] even after a drastic decrease in the liver mass [3][4][5]. Indeed, after partial hepatectomy the gluconeogenic capacity of the liver remnant increases.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have reported that the residual liver lobes after hepatectomy maintain all the liver functions necessary to keep homeostasis in normal organic levels despite the ongoing regeneration process 3,33.34 . In partially hepatectomized rats, plasma insulin concentrations have a significant decrease 35,36 , while the levels of glucagon increase 37,38 , which probably constitutes part of the homeostatic response resulting, among other things, in proper blood glucose levels 36 . In the group with omega-3 intake, as well as in the one with omega-6, plasma glucose values were significantly decreased ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%